Integrative approach to the psychodiagnosis of post-traumatic stress disorder among participants in the antiterrorist operation - Druz, O. V.; Grinevich, Ye. G.; Chernenko, I. O. (Journal of Education, Health and Sport, 2016)
Clinical-psychopathological („gold standardt“) and psychodiagnostic indexes in the participants of local combat actions in Ukraine have been investigated. The force of their interrelations and number were analyzed. On the ground of the results obtained the “Protocol of quantitative, psychodiagnostic, psychometric estimation of post-traumatic stress disorder and associated with it conditions in the participants of local combat actions” has been worked out. It contains the optimal amount of psycho-diagnostic techniques with proven sufficient degree of validity (effectiveness of post-traumatic stress disorders diagnostics) and allows to quantify psychopathology in the structure of PTSD and mental disorders, associated with it among the participants of local combat actions; ascertain mechanisms of self-reactive specific adaptive psychological and behavioral changes as a result of multiple stressors, including intense combat stress; medical and social consequences of PTSD (suicidal behavior, substance use, the impact of PTSD on the mental activity, cognitive and intellectual functions, inadequate and dysfunctional processing of stressful traumatic experiences); combat situation stressful factors and stressors. Application of this protocol will help to shape adequate medical directions and procedures of preventive, therapeutic interventions and rehabilitative measures.